The Phenomenon of The Spread of Ransomware Virus that Infects Bank Systems and Legal Protection for Victims Affected by Ransomware Attacks - Satria Dwi Andyka; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2024)
This research aims to understand the cases of Ransomware attacks within the banking sector. Rapid technological advance have significantly impacted the digital word, especially banking. The prevalence of Ransomware cases continues to increase each year due to the ineffectiveness of specific legal regulations governing ransomware cases. Additionally, there is a lack clarity regarding legal protection for victims affected by ransomware attacks. This study employs a normative juridical approach. Two sources of data are utilized: primary data source and secondary data. When viewed from Philipus M Hadjon's theoretical perspective, the research findings indicate ineffectiveness as it fails to fulfill other more general or universally applicable Legal Protection Theories. This implies a need for more consensus on legal protection. Many concentrates on specifics laws. This regulation of ransomware cases has not yet fully succeeded in reducing such incidents in Indonesia, as the number of cases continues to rise every year.